1966
DOI: 10.1113/jphysiol.1966.sp007811
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of high‐energy phosphates during active sodium and potassium interchange in frog muscle

Abstract: SUMMARY1. Potassium-depleted muscles have been analysed for cations, phosphocreatine, adenosine triphosphate and lactate before or after an exposure to a medium with 10 mm potassium salt.2. The net movements of sodium out and potassium in when the system is anaerobic but not otherwise poisoned are accompanied by break-down of phosphocreatine and formation of lactate.3. In bicarbonate media oligomycin has little perceptible effect upon these observed changes, which is taken to indicate that mitochondrial phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

1967
1967
1993
1993

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…In muscle, however, ATP can also be produced by a strong glycolytic system, by non-oxidative phosphorylation or by the creatine phosphate transfer reaction (Slater 1960). Thus Dydynska & Harris (1966) reported levels of phosphocreatine of 15-5 m-equiv/kg and of ATP of 2*6 m-equiv/kg in frog sartorius with Na content elevated by cold storage. When these muscles were incubated in the presence of oligomycin and in an atmosphere of nitrogen oxidativee phosphorylation and respiration inhibited), after 70 min and a net Na pumping of 22 /imole/g, ATP was reduced a little more than 10% and phosphocreatine dropped by 30 %, suggesting that muscles incubated in K-free conditions with 5 mm azide will show little change in ATP and phosphocreatine after 45 min.…”
Section: Discussionmentioning
confidence: 99%
“…In muscle, however, ATP can also be produced by a strong glycolytic system, by non-oxidative phosphorylation or by the creatine phosphate transfer reaction (Slater 1960). Thus Dydynska & Harris (1966) reported levels of phosphocreatine of 15-5 m-equiv/kg and of ATP of 2*6 m-equiv/kg in frog sartorius with Na content elevated by cold storage. When these muscles were incubated in the presence of oligomycin and in an atmosphere of nitrogen oxidativee phosphorylation and respiration inhibited), after 70 min and a net Na pumping of 22 /imole/g, ATP was reduced a little more than 10% and phosphocreatine dropped by 30 %, suggesting that muscles incubated in K-free conditions with 5 mm azide will show little change in ATP and phosphocreatine after 45 min.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of ADP under these anaerobic conditions remains, however, sufficient to maintain a normal Na-pumping rate and is even sufficient for the important Na-pumping induced by exposing K-depleted cells to a K-containing solution. Because in most tissues part of the02 consumption (Whittam, 1961;Baker & Connelly, 1966) or of the lactic acid production (Whittam & Ager, 1965;Dydynska & Harris, 1966) is proportional to the active Na-transport, these metabolic parameters have been used to assess the energetic requirements of the active Na-K transport. An activation of the Na-K pump induced in K-depleted cells by readmission of external K increases the anaerobic lactic acid production as a function of [K]0.…”
Section: Influence Of the Na-pump On The Metabolism In Normal Tissuesmentioning
confidence: 99%
“…However, the rapid turnover of ATP, the low permeability of cell membranes for P04 and the lack of knowledge on the exchange reactions between H2180 and ATP make this method difficult to use and decrease appreciably its reliability (Mommaerts, 1969). Another possibility is to inhibit the reactions responsible for the rephosphorylation of ADP and to follow the decrease of the ATP content in tissues under different experimental conditions (Dydynska & Harris, 1966). This method too has certainly in smooth muscle some severe drawbacks.…”
mentioning
confidence: 99%
“…The loading of pairs of frog sartorius muscles with sodium ions by overnight immersion in cold (40 C) K-free saline (90 mM-NaCl, 30 mM-NaHCO3, 1 mM-CaCl2) was carried out precisely as described before (Dydynska & Harris, 1966). When IAA was to be used in the Na extrusion period, the pair of muscles was exposed to 0 5 mm IAA in K-free solution at 200 C for 10 min previously, to allow time for penetration.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous paper Dydynska & Harris (1966) showed that the active exchange of Na for K by Na-loaded frog muscles took place with an apparent ratio of about 2x5 Na ions per equivalent high energy phosphate bond. It seemed desirable to supplement the results with some more complete analyses because (1) the changes in ADP were not measured and these are not necessarily equal and opposite to ATP changes, particularly in the presence of dinitrofluorobenzene (DNFB); and (2) with either iodoacetate (IAA) or DNFB the formation of fructose diphosphate can consume ATP (as noted by R. E. Davies, personal communication).…”
Section: Introductionmentioning
confidence: 98%